Designing for the next generation of augmented books. (27th October 2021) - Corrigan-Kavanagh, Emily; Frohlich, David; Yuan, Haiyue; Bober, Miroslaw
This paper presents an advanced process for designing "a-books"; augmented printed books with multimedia links presented on a nearby device. Although augmented paper is not new, our solution facilitates mass market use through industry standard publishing software that generates the a-book, and regular smartphones that play related digital media by optically recognising its ordinary paper pages through the phone's built-in camera. This augmented paper strategy informs new classifications of digital content within publication design, enabling new immersive reading possibilities. Complementary affordances of print and digital, and how these are combined and harnessed by a-books in comparison to previous augmented paper concepts are first discussed. Subsequently, an explanation of the workflow for designing a-books is described. The final discussion includes implications for content creators of paper-based publishing, and future research plans.